Expression of Puroindoline a in Durum Wheat Affects Milling and Pasting Properties - Wang, Qiong; Li, Yin; Sun, Fusheng; Li, Xiaoyan; Wang, Pandi; Yang, Guangxiao; He, Guangyuan (Frontiers in Plant Science, 2019)
Durum wheat has limited culinary utilizations partly due to its extremely hard kernel texture. Previously, we developed transgenic durum wheat lines with expression of the wildtype Puroindoline a (Pina) and characterized PINA’s effects on kernel hardness, total flour yield and dough mixing properties in durum wheat. The medium-hard kernel texture is potentially useful for exploring culinary applications of durum wheat. In the present study, we examined the milling parameters and flour attributes of the transgenic lines, including particle size distribution, damaged starch and water binding capacity. PINA expression results in increased break and reduction flour yield but decreased shorts. PINA expression also leads to finer flour particles and decreased starch damage. Interestingly, PINA transgenic lines showed increased peak viscosity and breakdown viscosity but leave other flour pasting parameters generally unaltered. PINA transgenic lines were associated with increased small monomeric proteins, appearing to affect gluten aggregation. Our data together with several previous results highlight distinct effects of PINs on pasting properties depending on species and variety. The medium-hard kernel texture together with improved pasting parameters may be valuable for producing a broader range of end-products from durum wheat.